ANALISIS KINERJA APARATUR DESA PADA KUALITAS PELAYANAN MASYARAKAT DI DESA BUSUNG KABUPATEN BINTAN - Armansyah Armansyah; Ahmad Yani; Agustinus Sihombing; Muqtafin Muqtafin; Tesar Nonanda; Betty Leindarita (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the performance of village officials on service quality at the Busung village office, Bintan district, and to find out what factors hinder employee performance on service quality at the Busung village office, Bintan district. This research method used by researchers is a qualitative research method. Data collection techniques using observation and interviews. Based on the results of the interviews, it can be concluded that the performance of the Busung village apparatus is good but needs to be improved. This is caused by several factors that hinder the achievement of the work results of the Busung village office apparatus, namely employee awareness of the